Antarctic bedrock topography uncertainty and ice sheet stability. Issue 13 (14th July 2015) - Gasson, E.; DeConto, R.; Pollard, D.
Abstract Antarctic bedrock elevation estimates have uncertainties exceeding 1 km in certain regions. Bedrock elevation, particularly where the bedrock is below sea level and bordering the ocean, can have a large impact on ice sheet stability. We investigate how present‐day bedrock elevation uncertainty affects ice sheet model simulations for a generic past warm period based on the mid‐Pliocene, although these uncertainties are also relevant to present‐day and future ice sheet stability. We perform an ensemble of simulations with random topographic noise added with various length scales and with amplitudes tuned to the uncertainty of the Bedmap2 data set. Total Antarctic ice sheet retreat in these simulations varies between 12.6 and 17.9 m equivalent sea level rise after 3 kyrs of warm climate forcing. This study highlights the sensitivity of ice sheet models to existing uncertainties in bedrock elevation and the ongoing need for new data acquisition.